2003
DOI: 10.1038/sj.bjc.6601052
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of patients with Hodgkin's disease following curative treatment: the routine CT scan is of little value

Abstract: A total of 10 -40% of patients with Hodgkin's disease relapse following initial curative therapy. Intensive follow-up is resource intensive and may identify false relapses. We performed a retrospective review of all patients with Hodgkin's disease treated at our centre between 1990 and 1999 to evaluate the utility of the components of follow-up. A total of 107 patients met the inclusion and exclusion criteria. The median age was 33 years and the median duration of follow-up 38 months. The total number of follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 6 publications
3
46
0
1
Order By: Relevance
“…The study reported by Pingali et al 11 compared the incidence of relapse in patients managed with clinical surveillance alone and in those who underwent routine surveillance imaging, reporting that differences between groups were not statistically significant (7.4% vs. 3.4%, p = 0.39). The two remaining studies reported that the proportion of relapses initially suspected by clinical manifestations ranged from a low of 13% 9 to a high of 64% 4 and that the proportion of relapses initially suspected by surveillance imaging ranged from a low of 8% 9 to a high of 27% 4 .…”
Section: Detection Of Relapsementioning
confidence: 99%
See 3 more Smart Citations
“…The study reported by Pingali et al 11 compared the incidence of relapse in patients managed with clinical surveillance alone and in those who underwent routine surveillance imaging, reporting that differences between groups were not statistically significant (7.4% vs. 3.4%, p = 0.39). The two remaining studies reported that the proportion of relapses initially suspected by clinical manifestations ranged from a low of 13% 9 to a high of 64% 4 and that the proportion of relapses initially suspected by surveillance imaging ranged from a low of 8% 9 to a high of 27% 4 .…”
Section: Detection Of Relapsementioning
confidence: 99%
“…Nine studies reported on the followup care of asymptomatic survivors of lymphoma who had received curative-intent treatment [4][5][6][7][8][9][10][11][12] . Two studies involving patients with nhl in complete remission detected a statistically significant difference in the number of relapses initially suspected by clinical manifestations (patient-reported symptoms or physical examination) compared with relapses initially suspected by imaging before clinical manifestation 10,12 .…”
Section: Detection Of Relapsementioning
confidence: 99%
See 2 more Smart Citations
“…5 Conclusions from previous studies support a restrictive use of routine surveillance imaging, as the majority of relapses are preceded by symptoms or abnormalities on clinical examination, but these studies mainly used conventional radiograms and not whole-body computed tomography (CT), which is now more commonly performed. 6,7 Routine CT surveillance, however, also appears to have limited value; in a study by Dryver et al, only 9% of HL relapses were diagnosed by CT. 8 Besides, CT surveillance is probably not cost-effective and could decrease quality of life mainly by increasing patients' anxiety. 9,10 Thus, the extensive use of routine surveillance imaging for HL patients remains controversial, with no international consensus.…”
Section: Introductionmentioning
confidence: 99%